Cadmium Contamination in Rice and Associated Human Health Risk - Mukta Tamanna Akther; Hoque Mohammad Anamul; Shimo Farjana Jannat; Islam Shofiqul (Agriculture)
Rice (Oryza sativa L.), the traditional food for the Bangladeshi population, serves as a significant disclosure pathway of cadmium for humans. A few studies have explored cadmium levels in different rice varieties in Bangladesh. The study examined the impacts of cadmium pollution on growth, and productivity and evaluated the varietal resistance. Cadmium was added to the soil at 15 mg/kg. A pot experiment involving nine T-aman rice varieties was conducted at 0 (control) and 15 mg Cd/kg soil. Cadmium toxicity led to reduced quantity and quality of rice production. Cadmium pollution enhanced the grain cadmium levels while depleting the amounts of nitrogen, phosphorus, potassium, and sulphur. Local varieties and BRRI dhan72 exhibited the lowest grain cadmium concentration when grown with 0 mg/kg cadmium in the soil, while BRRI dhan52 (2.94 mg/kg) showed the highest with 15 mg/kg cadmium in the soil. The average daily intake of cadmium from rice grain was higher with 15 mg/kg cadmium addition. All rice varieties showed high HQ (Hazard Quotient) and ILCR (Incremental Lifetime Cancer Risk) values under 15 mg/kg cadmium in soil. The HQ and ILCR values ranged from 2.39 to 16.09, and 0.36 × 10−4 to 2.41 × 10−4, respectively, for a Bangladeshi adult due to the application of 15 mg/kg cadmium. The highest HQ (16.09) and ILCR (2.41×10−4) values were obtained for BRRI dhan52 at 15 mg/kg cadmium for adults. The susceptibility of the varieties due to 15 mg/kg cadmium may be ranked as BRRI dhan52>Binadhan-23>BRRI dhan79>Binadhan-12>BRRI dhan62>BRRI dhan71>Zeeramala>BRRI dhan72>Local HYV.